Prequels, Sequels and Everything Else: Transmedia Storytelling and the Game of Thrones Universe - Sipos, Nikolett (AMERICANA E-journal of American Studies in Hungary, 2024)
Game of Thrones has become one of the most popular fantasy franchises of the 21st century. The starting point of this universe was George R.R. Martin’s epic fantasy saga, A Song of Ice and Fire, which became a worldwide success thanks to the HBO adaptation titled Game of Thrones (2011-2019), created by David Benioff and D.B. Weiss. Since then, several other adaptations have been born and are currently in the making, including media campaigns (The Maester’s Path, 2011), books (A Knight of the Seven Kingdoms, 2005; The World of Ice and Fire, 2014; Fire & Blood, 2018), podcasts (Pod of Thrones, Game of Owns), and games (A Game of Thrones: Genesis, 2011; Game of Thrones, 2014). The visual storyworld of the franchise has been further expanded by the HBO prequel House of the Dragon (2022– ), but there are other Westeros series in the making as well. Thus, with all the media incarnations, Game of Thrones became a true example of a transmedia story – in this paper, I am going to introduce how these media entries are linked in this huge transmedia universe, and how they fit into the world of media convergence.